Assessment of slurry consolidation using index properties. Issue 1 (January 2013) - Chandra Paul, A; Azam, S
Abstract : Several engineering applications involve dilute slurries such as mine tailings, municipal sludges, dredged materials, and hydraulic fills. An assessment of the consolidation behavior is pivotal for minimizing the environmental footprint of these fine-grained slurries at the outset of deposition. The volume compressibility and hydraulic conductivity properties during dewatering are governed by complex solid–liquid interactions that are captured by the index properties. This study focused on analyzing slurry consolidation in conjunction with soil consistency. Results indicated that the consistency limits for sedimentary clays covered a wide range due to the presence of various clay minerals. Sesquioxide coating of clays and dominance of non-clays resulted in lower liquid and plastic limits for residual soils. The relatively high limits for oil sand tailings were due to residual bitumen that imparts thixotropy and lubrication. The analyzed consolidation data ( σ ′ = 1 kPa to 450 kPa, e = 10 to 1, and k = 10 −4 to 10 −9 cm s −1 ) for each material group fitted best to a decreasing power law for compressibility and an increasing power law for conductivity. The 99% confidence intervals were wide at low σ ′ and high e and gradually narrowed down with a change in these parameters. The volume compressibility coefficients ( A and B ) linearly varied with I p whereas the hydraulic conductivity coefficients ( C and D ) followed decreasing power law functions of I p . Strong agreements between measured and modeled data were obtained for both void ratio ( R 2 = 0·98) and hydraulic conductivity ( R 2 = 0·99).